2017
DOI: 10.1038/s41598-017-05074-w
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous melatonin promotes rhythmic recruitment of neutrophils toward an injury in zebrafish

Abstract: Neutrophil recruitment to injured tissue appears to be an evolutionarily conserved strategy for organisms to fight against exogenous insults. Recent studies have shown rhythmic migration of neutrophils and several factors, including melatonin, have been implicated in regulating this rhythmic migration. The mechanisms underlying how endogenous melatonin regulates rhythmic neutrophils migration, however, are unclear. Here we generated a zebrafish annat2 mutant that lacks endogenous melatonin and, subsequently, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…For instance, several immune markers including peroxidase, phagocytic ability and cytotoxic activity of head kidney leucocytes as well as the expression of immune genes in head kidney (il-1β, major histocompatibility complex, and interferon-regulatory factor-1) are increased in gilthead seabream (Sparus aurata) following intraperitoneal injection of melatonin 20 . And, in zebrafish, endogenous melatonin enhances neutrophil migration following increase in cytokine expressions such as Il-8 and Il-1β 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, several immune markers including peroxidase, phagocytic ability and cytotoxic activity of head kidney leucocytes as well as the expression of immune genes in head kidney (il-1β, major histocompatibility complex, and interferon-regulatory factor-1) are increased in gilthead seabream (Sparus aurata) following intraperitoneal injection of melatonin 20 . And, in zebrafish, endogenous melatonin enhances neutrophil migration following increase in cytokine expressions such as Il-8 and Il-1β 22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, such immunomodulatory effects of melatonin have little been investigated in fish. Nevertheless, the available information supports an immune regulation by the melatonin hormone in teleosts 3,[19][20][21][22] . In pike perch, a potential dual action of cortisol and melatonin hormones on immune defenses was described 23,24 .…”
mentioning
confidence: 99%
“…The avian analogue of neutrophils, heterophils, is also observed to have a diurnal acrophase [66], whilst neutrophil injury recruitment in fish also has a circadian phenotype [87] suggesting these features are well preserved in different animals. The latter is influenced by melatonin, which has extensive pathways, reviewed with respect to immunity and inflammation previously [12,14,101,110].…”
Section: Neutrophilsmentioning
confidence: 99%
“…This effect was counteracted significantly when treated with melatonin as shown in the elevated expression of redox sensor–nuclear factor erythroid–derived factor 2 (Nrf2), decreased expression of thymic stromal lymphopoietin (TSLP), and up‐regulation of antioxidant genes‐heme oxygenase 1 (HO‐1) and nicotinamide adenine dinucleotide (phosphate) NAD(P)H‐quinone oxidoreductase 1 (NQO) 94 . Using aanat2 −/− zebrafish larvae lacking melatonin, Ren et al 95 suggested endogenous melatonin promotes migration of neutrophils through cytokine signaling, in particular the downregulation of inflammatory cytokines IL‐1β and IL‐8. Recently, melatonin was reported to disrupt the IL‐1β/NF‐κB/NLRP3 inflammasome positive feedback loop leading to the inhibition of NLR pyrin domain–containing 3 (NLRP3), p20, and IL‐1β synthesis 96 .…”
Section: Effects and Action Mechanisms Of Melatonin And Histamine In Mcsmentioning
confidence: 99%